Silicon-carbon composite material as well as preparation method and application thereof

Through the emulsion compound phenolic resin and sodium silicate, and the reaction of curing, carbonization and magnesium heat reaction, prepare a silicon carbon composite material with excellent electrochemical properties, and solves the problem of complex and cost of CVD gas deposition silicon carbon. The production of low -cost and efficient silicon carbon composite materials.

CN119340358APending Publication Date: 2025-01-21HEFEI GUOXUAN HIGH TECH POWER ENERGY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411325050.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

CVD vapor-phase deposition silicon carbon production equipment has high requirements, difficulty in storage and transportation of raw materials, and complex deposition process, which limits its rapid promotion in the market.

Method used

The emulsion method is used to uniformly compound the phenolic resin and sodium silicate. The reaction of solidification, carbonization and magnesium heat reduction reaction is prepared to prepare silicon carbon composite materials with excellent electrochemical properties.

Benefits of technology

The simplification and cost of preparation process are realized, and it is suitable for quantitative production of silicon carbon composite materials, and has high ratio, circulating stability and magnification performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340358A_ABST
    Figure CN119340358A_ABST
Patent Text Reader

Abstract

The invention provides a silicon-carbon composite material as well as a preparation method and application thereof, and relates to the technical field of lithium ion batteries. The preparation method of the silicon-carbon composite material comprises the following steps: S1, carrying out homogenization treatment on a phenolic resin solution, a silicic acid solution and a nonionic emulsifier to obtain a primary emulsion; s2, curing the primary emulsion to obtain cured particles, and carbonizing the cured particles to obtain carbonized particles; and S3, carrying out magnesiothermic reduction reaction on the carbonized particles, and washing to obtain the silicon-carbon composite material. The silicon-carbon composite material prepared by the preparation method disclosed by the invention has relatively high specific capacity, cycling stability and rate capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a silicon-carbon composite material and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries have become one of the most popular energy storage systems due to their long service life, high specific capacity and environmental friendliness. They are widely used in small electronic devices, aerospace and other fields. Commercial lithium-ion batteries usually use layered transition metal oxides as positive electrodes and graphite as negative electrodes. Although the specific capacity of graphite negative electrodes is close to the theoretical value, with the rapid development of electric vehicles and other electric means of transportation, the power and energy density of traditional lithium-ion batteries are gradually unable to meet the needs of consumers. Crystalline silicon is a potential negative electrode material that can provide up to 3579mA hg at room temperature. -1 The theoretical lithium insertion capacity is much higher than the most widely used graphite (372mA hg -1 ). In addition, silicon has the advantages of high reserves, environmental friendliness, and low production costs. However, there is a serious problem with silicon negative electrodes: when lithium ions are fully embedded in the silicon matrix, the silicon matrix will undergo severe volume expansion (>300%), which will cause the silicon negative electrode to pulverize after multiple charge and discharge cycles, and then cause the silicon to lose electrical contact with the current collector, and the battery capacity will decay rapidly. At the same time, the volume effect of the silicon negative electrode during the cycle process will cause the SEI film to rupture and regenerate repeatedly, which will lead to a decrease in the coulombic efficiency of the battery and an increase in the ion transfer resistance.

[0003] Therefore, in order to realize the commercial application of silicon negative electrode, solving its volume effect is the primary issue. Researchers have found that in order to solve the problems of expansion and failure faced by silicon-based negative electrodes, academia and industry have developed a variety of silicon-based negative electrode modification methods, mainly including silicon oxidation, nano-sizing, composite, porosification, alloying, pre-lithiation, pre-magnesiation, etc., which are mainly divided into silicon oxygen and silicon carbon in major categories. Among the subdivided technical routes, there are currently three routes that have been industrialized. The first is the grinding method nano-silicon carbon route, the second is the silicon oxygen route (first-generation silicon oxygen and pre-lithiation silicon oxygen), and the third is the CVD vapor deposition silicon carbon route. Today, on the basis of the other two silicon negative electrode technical routes facing certain bottlenecks, with the breakthrough of vapor deposition silicon carbon products and the verification of full battery performance, downstream battery cell factories have gradually shifted their focus to CVD vapor deposition silicon carbon. However, there are many technical barriers and industrial difficulties in vapor deposition of silicon carbon, including the selection of porous carbon, deposition equipment and deposition process, etc. The preparation process has strict equipment requirements and requires the use of hazardous silane gas, which limits the rapid promotion of its new silicon-carbon negative electrode in the market. Summary of the invention

[0004] The present invention solves the problems of high requirements for CVD vapor deposition silicon-carbon production equipment, difficulty in raw material storage and transportation, and complex deposition process, and provides a method for preparing silicon-carbon composite materials with low cost, simple preparation process, and suitable for mass production, and its application in lithium-ion batteries. The silicon-carbon composite materials of the present invention have excellent electrochemical properties.

[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0006] A method for preparing a silicon-carbon composite material proposed by the present invention comprises the following steps:

[0007] S1, homogenizing the phenolic resin solution, the silicic acid solution, and the nonionic emulsifier to obtain a primary emulsion;

[0008] S2, curing the primary emulsion to obtain solidified particles, and carbonizing the solidified particles to obtain carbonized particles;

[0009] S3, subjecting the carbonized particles to a magnesium thermal reduction reaction, and washing them to obtain a silicon-carbon composite material.

[0010] The present invention first adopts a specific emulsification and curing process to prepare a phenolic resin-coated silica emulsion, so as to achieve uniform dispersion and stable encapsulation of silicate particles in a phenolic resin matrix; then, the emulsion is subjected to a carbonization treatment to convert the phenolic resin into a stable carbon coating layer; finally, the silicon dioxide coated in the carbon layer is reduced to nano-silicon particles through a magnesium thermal reduction process; the obtained carbon-coated nano-silicon material, i.e., a silicon-carbon composite material, has excellent electrochemical properties and cycle stability, and is an ideal negative electrode material for lithium-ion batteries. The preparation method of the present invention is simple, efficient, and can be mass-produced, and the product performance can be optimized by regulating parameters such as emulsification, curing, carbonization, and reduction conditions to meet the needs of different types of lithium-ion batteries.

[0011] Preferably, in S1, the preparation of the silicic acid solution comprises dissolving sodium silicate dihydrate in deionized water and adjusting the pH to 9-10.

[0012] Preferably, in said S1, the mass fraction of the silicic acid solution is 5-15%.

[0013] The mass fraction of silicic acid solution within a certain range is conducive to the prepared silicon-carbon composite material having higher specific capacity, cycle stability and rate performance.

[0014] Preferably, in S1, the preparation of the phenolic resin solution comprises reacting formaldehyde and phenol in a molar ratio of (1-1.4):1 at 60-70° C. for 2-3 hours under the action of an alkaline catalyst.

[0015] Preferably, in S1, the nonionic emulsifier is selected from one or more of polyoxyethylene alcohols and polyoxyethylene esters commonly used in industry.

[0016] Non-ionic emulsifiers can evenly disperse two immiscible substances, silicic acid and phenolic resin solution. Secondly, non-ionic emulsifiers have good stability and can maintain an emulsified state for a long time under certain conditions.

[0017] Preferably, in S1, the homogenization treatment comprises treatment under high shear conditions for 5-10 min.

[0018] The homogenization treatment achieves uniform dispersion and stable encapsulation of silicate particles in the phenolic resin matrix. The carbon layer of the silicon-carbon composite material prepared in this way can effectively inhibit the expansion of silicon particles during the circulation process.

[0019] Preferably, in the S1, the mass ratio of phenolic resin, sodium silicate dihydrate and nonionic emulsifier is 8:13:(0-0.4).

[0020] Preferably, in S2, the solidification treatment includes adjusting the pH of the primary emulsion and heating it to T1.

[0021] More preferably, the pH is adjusted to 3-6.

[0022] The phenolic resin in the primary emulsion is cross-linked and cured by adjusting the pH to acidic and heating to obtain a structure in which the cured phenolic resin wraps the silicic acid particles, which serves as a precursor of the silicon-carbon composite material.

[0023] More preferably, the T1 temperature is 80-120°C.

[0024] Preferably, in S2, the carbonization treatment includes heating and keeping the solidified particles warm in an inert gas.

[0025] The phenolic resin is converted into a stable carbon coating by carbonization and silicic acid is decomposed into silicon dioxide and water, and the obtained carbonized particles are carbon-coated silicon dioxide.

[0026] More preferably, the inert gas includes one or more of nitrogen and argon.

[0027] More preferably, the heating and heat preservation comprises heat preservation at 500-1000° C. for 1-5 hours.

[0028] Preferably, in said S3, the magnesium thermal reduction reaction comprises mixing the carbonized particles with magnesium powder and heating and keeping the mixture warm.

[0029] The magnesium thermal reduction reaction reduces the silicon dioxide coated in the carbon layer into nano-silicon particles, which shrink in volume and form a uniform egg-yolk structure with the silicon particles and the carbon shell.

[0030] More preferably, the mass of the magnesium powder is 2-3 times the mass of silicate.

[0031] More preferably, the heating and heat preservation comprises heat preservation at 500-800° C. for 1-3 hours.

[0032] Controlling the temperature and time of heating and insulation helps the prepared silicon-carbon composite material to have higher specific capacity, cycle stability and rate performance.

[0033] Preferably, in S3, the washing is pickling, and the pickling acid solution is 1 mol / L hydrochloric acid solution.

[0034] The present invention also provides a silicon-carbon composite material prepared by the above preparation method.

[0035] An application of the silicon-carbon composite material or the silicon-carbon composite material prepared by the above preparation method in a lithium-ion battery.

[0036] The beneficial effects of the present invention are:

[0037] The present invention uses phenolic resin as a carbon source and sodium silicate as a silicon source, uses an emulsion method to uniformly compound the silicon source and the carbon source, and obtains a silicon-carbon composite material with a diameter of 2-5 μm through curing, carbonization and reduction. The raw materials used in the present invention are low in price, the preparation process is simple and easy to operate, and is suitable for quantitative production of silicon-carbon composite materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is the X-ray diffraction spectrum of the silicon-carbon composite material prepared in Example 1.

[0039] Figure 2 (a) is a scanning electron microscope image of the silicon-carbon composite material prepared in Example 1 at a magnification of 20,000 times, and (b) is a scanning electron microscope image at a magnification of 50,000 times.

[0040] Figure 3 (a) is a 20,000-fold scanning electron microscope image of the cross section of the silicon-carbon composite material prepared in Example 1, and (b) is a 50,000-fold scanning electron microscope image of the cross section.

[0041] Figure 4 This is the charge and discharge curve of the silicon-carbon composite material prepared in Example 1 at a current density of 0.1C. DETAILED DESCRIPTION

[0042] The technical solution of the present invention is described in detail through specific embodiments.

[0043] Unless otherwise specified, the materials, reagents, etc. used in the following examples and comparative examples can be obtained from commercial sources.

[0044] Example 1

[0045] A method for preparing a silicon-carbon composite material comprises the following steps:

[0046] S1. Formaldehyde and phenol are prepared in a molar ratio of 1.3:1 to obtain a mixture with a total mass of 8 g. The mixture is reacted at 60°C for 2 h under the catalytic action of sodium hydroxide to obtain a phenolic resin solution. 13 g of sodium silicate dihydrate is dissolved in deionized water to form a 10% silicic acid solution, and the pH is adjusted to 9 to obtain a silicic acid solution. The phenolic resin solution is added to the silicic acid solution, and 0.4 g of polyoxyethylene alcohol is added. The mixture is stirred with a glass rod for 5 min, and then treated under high shear conditions for 10 min to obtain a primary emulsion.

[0047] S2, adjusting the pH of the primary emulsion to 6, and heating it to 120° C. to obtain solidified particles, heating the solidified particles to 800° C. at 5° C. / min in an argon atmosphere and maintaining it for 3 hours to obtain carbonized particles;

[0048] S3. Mix the carbonized particles with magnesium powder, wherein the amount of magnesium powder added is 3 times the mass of silicic acid, heat to 650°C at 2°C / min in an argon atmosphere and maintain for 2 hours, and remove impurities by acid washing to obtain a silicon-carbon composite material.

[0049] Example 2

[0050] A method for preparing a silicon-carbon composite material comprises the following steps:

[0051] S1. Formaldehyde and phenol are prepared in a molar ratio of 1.3:1 to obtain a mixture with a total mass of 8 g. The mixture is reacted at 60°C for 2 h under the catalytic action of sodium hydroxide to obtain a phenolic resin solution. 13 g of sodium silicate dihydrate is dissolved in deionized water to form a 15% silicic acid solution, and the pH is adjusted to 9 to obtain a silicic acid solution. The phenolic resin solution is added to the silicic acid solution, and 0.4 g of polyoxyethylene alcohol is added. The mixture is stirred with a glass rod for 5 min, and then treated under high shear conditions for 10 min to obtain a primary emulsion.

[0052] S2, adjusting the pH of the primary emulsion to 6, and heating it to 120° C. to obtain solidified particles, heating the solidified particles to 800° C. at 5° C. / min in an argon atmosphere and maintaining it for 3 hours to obtain carbonized particles;

[0053] S3. Mix the carbonized particles with magnesium powder, wherein the amount of magnesium powder added is 3 times the mass of silicic acid, heat to 650°C at 2°C / min in an argon atmosphere and maintain for 2 hours, and remove impurities by acid washing to obtain a silicon-carbon composite material.

[0054] Example 3

[0055] A method for preparing a silicon-carbon composite material comprises the following steps:

[0056] S1. Formaldehyde and phenol are prepared in a molar ratio of 1.3:1 to obtain a mixture with a total mass of 8 g. The mixture is reacted at 60°C for 2 h under the catalytic action of sodium hydroxide to obtain a phenolic resin solution. 13 g of sodium silicate dihydrate is dissolved in deionized water to form a 5% silicic acid solution, and the pH is adjusted to 9 to obtain a silicic acid solution. The phenolic resin solution is added to the silicic acid solution, and 0.4 g of polyoxyethylene alcohol is added. The mixture is stirred with a glass rod for 5 min, and then treated under high shear conditions for 10 min to obtain a primary emulsion.

[0057] S2, adjusting the pH of the primary emulsion to 6, and heating it to 120° C. to obtain solidified particles, heating the solidified particles to 800° C. at 5° C. / min in an argon atmosphere and maintaining it for 3 hours to obtain carbonized particles;

[0058] S3. Mix the carbonized particles with magnesium powder, wherein the amount of magnesium powder added is 3 times the mass of silicic acid, heat to 650°C at 2°C / min in an argon atmosphere and maintain for 2 hours, and remove impurities by acid washing to obtain a silicon-carbon composite material.

[0059] Example 4

[0060] A method for preparing a silicon-carbon composite material comprises the following steps:

[0061] S1. Formaldehyde and phenol are prepared in a molar ratio of 1.3:1 to obtain a mixture with a total mass of 8 g. The mixture is reacted at 60°C for 2 h under the catalytic action of sodium hydroxide to obtain a phenolic resin solution. 13 g of sodium silicate dihydrate is dissolved in deionized water to form a 10% silicic acid solution, and the pH is adjusted to 9 to obtain a silicic acid solution. The phenolic resin solution is added to the silicic acid solution, and 0.3 g of polyoxyethylene alcohol is added. The mixture is stirred with a glass rod for 5 min, and then treated under high shear conditions for 10 min to obtain a primary emulsion.

[0062] S2, adjusting the pH of the primary emulsion to 6, and heating it to 120° C. to obtain solidified particles, heating the solidified particles to 800° C. at 5° C. / min in an argon atmosphere and maintaining it for 3 hours to obtain carbonized particles;

[0063] S3. Mix the carbonized particles with magnesium powder, wherein the amount of magnesium powder added is 3 times the mass of silicic acid, heat to 650°C at 2°C / min in an argon atmosphere and maintain for 2 hours, and remove impurities by acid washing to obtain a silicon-carbon composite material.

[0064] Example 5

[0065] A method for preparing a silicon-carbon composite material comprises the following steps:

[0066] S1. Formaldehyde and phenol are prepared in a molar ratio of 1.3:1 to obtain a mixture with a total mass of 8 g. The mixture is reacted at 60°C for 2 h under the catalytic action of sodium hydroxide to obtain a phenolic resin solution. 13 g of sodium silicate dihydrate is dissolved in deionized water to form a 15% silicic acid solution, and the pH is adjusted to 9 to obtain a silicic acid solution. The phenolic resin solution is added to the silicic acid solution, and 0.2 g of polyoxyethylene alcohol is added. The mixture is stirred with a glass rod for 5 min, and then treated under high shear conditions for 10 min to obtain a primary emulsion.

[0067] S2, adjusting the pH of the primary emulsion to 6, and heating it to 120° C. to obtain solidified particles, heating the solidified particles to 800° C. at 5° C. / min in an argon atmosphere and maintaining it for 3 hours to obtain carbonized particles;

[0068] S3. Mix the carbonized particles with magnesium powder, wherein the amount of magnesium powder added is 3 times the mass of silicic acid, heat to 650°C at 2°C / min in an argon atmosphere and maintain for 2 hours, and remove impurities by acid washing to obtain a silicon-carbon composite material.

[0069] Example 6

[0070] A method for preparing a silicon-carbon composite material comprises the following steps:

[0071] S1. Formaldehyde and phenol are prepared in a molar ratio of 1.3:1 to obtain a mixture with a total mass of 8 g. The mixture is reacted at 60°C for 2 h under the catalytic action of sodium hydroxide to obtain a phenolic resin solution. 13 g of sodium silicate dihydrate is dissolved in deionized water to form a 10% silicic acid solution, and the pH is adjusted to 9 to obtain a silicic acid solution. The phenolic resin solution is added to the silicic acid solution, and 0.4 g of polyoxyethylene alcohol is added. The mixture is stirred with a glass rod for 5 min, and then treated under high shear conditions for 10 min to obtain a primary emulsion.

[0072] S2, adjusting the pH of the primary emulsion to 6, and heating it to 120° C. to obtain solidified particles, heating the solidified particles to 900° C. at 5° C. / min in an argon atmosphere and maintaining it for 3 hours to obtain carbonized particles;

[0073] S3. Mix the carbonized particles with magnesium powder, wherein the amount of magnesium powder added is 3 times the mass of silicic acid, heat to 650°C at 2°C / min in an argon atmosphere and maintain for 2 hours, and remove impurities by acid washing to obtain a silicon-carbon composite material.

[0074] Example 7

[0075] A method for preparing a silicon-carbon composite material comprises the following steps:

[0076] S1. Formaldehyde and phenol are prepared in a molar ratio of 1.3:1 to obtain a mixture with a total mass of 8 g. The mixture is reacted at 60°C for 2 h under the catalytic action of sodium hydroxide to obtain a phenolic resin solution. 13 g of sodium silicate dihydrate is dissolved in deionized water to form a 10% silicic acid solution, and the pH is adjusted to 9 to obtain a silicic acid solution. The phenolic resin solution is added to the silicic acid solution, and 0.4 g of polyoxyethylene alcohol is added. The mixture is stirred with a glass rod for 5 min, and then treated under high shear conditions for 10 min to obtain a primary emulsion.

[0077] S2, adjusting the pH of the primary emulsion to 6, and heating it to 120° C. to obtain solidified particles, heating the solidified particles to 700° C. at 5° C. / min in an argon atmosphere and maintaining it for 3 hours to obtain carbonized particles;

[0078] S3. Mix the carbonized particles with magnesium powder, wherein the amount of magnesium powder added is 3 times the mass of silicic acid, heat to 650°C at 2°C / min in an argon atmosphere and maintain for 2 hours, and remove impurities by acid washing to obtain a silicon-carbon composite material.

[0079] Comparative Example 1

[0080] A method for preparing a silicon-carbon composite material comprises the following steps:

[0081] S1. Formaldehyde and phenol are prepared in a molar ratio of 1.3:1 to obtain a mixture with a total mass of 8 g, and reacted at 60° C. for 2 h under the catalytic action of sodium hydroxide to obtain a phenolic resin solution; 13 g of sodium silicate dihydrate is dissolved in deionized water to form a 10% silicic acid solution, and the pH is adjusted to 9 to obtain a silicic acid solution; the phenolic resin solution is added to the silicic acid solution, stirred with a glass rod for 5 min, and then treated under high shear conditions for 10 min to obtain a primary emulsion;

[0082] S2, adjusting the pH of the primary emulsion to 6, and heating it to 120° C. to obtain solidified particles, heating the solidified particles to 800° C. at 5° C. / min in an argon atmosphere and maintaining it for 3 hours to obtain carbonized particles;

[0083] S3. Mix the carbonized particles with magnesium powder, wherein the amount of magnesium powder added is 3 times the mass of silicic acid, heat to 650°C at 2°C / min in an argon atmosphere and maintain for 2 hours, and remove impurities by acid washing to obtain a silicon-carbon composite material.

[0084] Comparative Example 2

[0085] A method for preparing a silicon-carbon composite material comprises the following steps:

[0086] S1. Formaldehyde and phenol are prepared in a molar ratio of 1.3:1 to obtain a mixture with a total mass of 8 g. The mixture is reacted at 60°C for 2 h under the catalytic action of sodium hydroxide to obtain a phenolic resin solution. 13 g of sodium silicate dihydrate is dissolved in deionized water to form a 10% silicic acid solution, and the pH is adjusted to 9 to obtain a silicic acid solution. The phenolic resin solution is added to the silicic acid solution, and 0.4 g of tetradecyltrimethylammonium chloride is added. The mixture is stirred with a glass rod for 5 min, and then treated under high shear conditions for 10 min to obtain a primary emulsion.

[0087] S2, adjusting the pH of the primary emulsion to 6, and heating it to 120° C. to obtain solidified particles, heating the solidified particles to 800° C. at 5° C. / min in an argon atmosphere and maintaining it for 3 hours to obtain carbonized particles;

[0088] S3. Mix the carbonized particles with magnesium powder, wherein the amount of magnesium powder added is 3 times the mass of silicic acid, heat to 650°C at 2°C / min in an argon atmosphere and maintain for 2 hours, and remove impurities by acid washing to obtain a silicon-carbon composite material.

[0089] Comparative Example 3

[0090] A method for preparing a silicon-carbon composite material comprises the following steps:

[0091] S1. Formaldehyde and phenol are prepared in a molar ratio of 1.3:1 to obtain a mixture with a total mass of 8 g. The mixture is reacted at 60°C for 2 h under the catalytic action of sodium hydroxide to obtain a phenolic resin solution. 9.6 g of methyl orthosilicate is dissolved in anhydrous ethanol to form a 10% methyl orthosilicate solution. The pH is adjusted to 9 to obtain a silicic acid solution. The phenolic resin solution is added to the silicic acid solution, and 0.4 g of polyoxyethylene alcohol is added. The mixture is stirred with a glass rod for 5 min, and then treated under high shear conditions for 10 min to obtain a mixed solution.

[0092] S2, adjusting the pH of the primary emulsion to 6, and heating it to 120° C. to obtain solidified particles, heating the solidified particles to 800° C. at 5° C. / min in an argon atmosphere and maintaining it for 3 hours to obtain carbonized particles;

[0093] S3. Mix the carbonized particles with magnesium powder, wherein the amount of magnesium powder added is 3 times the mass of silicic acid, heat to 650°C at 2°C / min in an argon atmosphere and maintain for 2 hours, and remove impurities by acid washing to obtain a silicon-carbon composite material.

[0094] The silicon-carbon composite material prepared in Example 1 was subjected to an X-ray diffraction (XRD) test, and the test results are as follows: Figure 1 As shown in the figure, it can be seen that the diffraction peak of crystalline silicon appears in the XRD spectrum of the electrode, indicating that crystalline silicon is successfully prepared by this method.

[0095] The silicon-carbon composite material prepared in Example 1 was tested by scanning electron microscope, and the test results are as follows: Figure 2 a. Figure 2 As shown in b, it can be seen from the figure that the material has a spherical morphology and the particle size is relatively uniform.

[0096] The silicon-carbon composite material prepared in Example 1 was subjected to a cross-sectional scanning electron microscope test, and the test results are as follows: Figure 3 a. Figure 3 As shown in b, it can be seen from the figure that there are no obvious hole defects in the cross section of the material.

[0097] The silicon-carbon composite material prepared above was used as the working electrode, the metal lithium sheet was used as the counter electrode, the polypropylene film was used as the diaphragm, and the 1 mol / L lithium hexafluorophosphate solution (wherein the solvent was a mixture of ethylene carbonate and diethyl carbonate in a volume ratio of 1:1) was used as the electrolyte. The CR2025 button cell was assembled in an argon-filled glove box for electrochemical performance testing. The discharge cut-off voltage was 0.005V, the charge cut-off voltage was 1.5V, and the charge and discharge test was carried out at a current density of C / 10. The results are recorded in Table 1.

[0098] Table 1

[0099]

[0100] It can be seen from the data in Table 1 that the lithium-ion battery assembled with the silicon-carbon composite material prepared by the present invention has a higher specific capacity, first-cycle efficiency and lower resistivity, indicating that the silicon-carbon composite material provided by the present invention has excellent electrochemical properties. Through data comparison, it can be seen that the silicon-carbon composite material prepared by the present invention has the highest specific capacity, the best cycle stability and rate performance when the optimal reaction temperature in the magnesium thermal reduction reaction is 650°C, the mass ratio of silicic acid to metallic magnesium is 1:3, and the mass fraction of the silicic acid solution is 10%.

[0101] like Figure 4 As shown, Figure 4 This is the charge and discharge curve of the silicon-carbon composite material prepared in Example 1 at a current density of 0.1C, with a discharge cut-off voltage of 0.005V, a discharge capacity of 2105.8mAh / g, a charge cut-off voltage of 1.5V, a charge capacity of 1963.2mAh / g, and a first efficiency of 0.005V of 93.2%.

[0102] In summary, the silicon-carbon composite material provided by the present invention has excellent electrochemical properties.

[0103] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a silicon-carbon composite material, characterized in that: The steps include: S1, homogenizing the phenolic resin solution, the silicic acid solution, and the nonionic emulsifier to obtain a primary emulsion; S2, curing the primary emulsion to obtain solidified particles, and carbonizing the solidified particles to obtain carbonized particles; S3, subjecting the carbonized particles to a magnesium thermal reduction reaction, and washing them to obtain a silicon-carbon composite material.

2. The preparation method according to claim 1, characterized in that: In the S1, the mass fraction of the silicic acid solution is 5-15%.

3. The preparation method according to claim 1, characterized in that: In the above-mentioned S1, the homogenization treatment comprises treatment under high shear conditions for 5-10 minutes.

4. The preparation method according to claim 1, characterized in that: In the above-mentioned S2, the solidification treatment includes adjusting the pH of the primary emulsion and heating it to T1.

5. The preparation method according to claim 1, characterized in that: In the above-mentioned S2, the carbonization treatment includes heating and keeping the solidified particles warm in an inert gas.

6. The preparation method according to claim 1, characterized in that: In the above-mentioned S3, the magnesium thermal reduction reaction comprises mixing the carbonized particles with magnesium powder and heating and keeping the mixture warm.

7. The preparation method according to claim 6, characterized in that: The heating and heat preservation includes heat preservation at 500-800°C for 1-3h.

8. A silicon-carbon composite material, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the silicon-carbon composite material according to claim 8 or the silicon-carbon composite material prepared by the preparation method according to any one of claims 1 to 7 in a lithium-ion battery.

Citation Information

Patent Citations

  • Mesoporous carbon / silicon composite anode material and preparation method thereof

    CN102867944A

  • Core-shell silicon carbon composite negative electrode material for high-capacity type lithium ion battery and preparation method therefor

    CN105489855A

  • Micron silicon-carbon composite material for negative electrode of lithium ion battery and preparation method of micron silicon-carbon composite material

    CN115241426A

  • Negative electrode composite material as well as preparation method and application thereof

    CN118486804A

  • Method for preparing mesoporous carbon material

    CN1821182A